Multifactorial interventions for preventing falls in older people living in the community: a systematic review and meta-analysis of 41 trials and almost 20 000 participants - Hopewell, S; Copsey, B; Nicolson, P; Adedire, B; Boniface, G; Lamb, S (BMJ Publishing Group, 2019)
OBJECTIVE:To assess the longer term effects of multifactorial interventions for preventing falls in older people living in the community, and to explore whether prespecific trial-level characteristics are associated with greater fall prevention effects. DESIGN:Systematic review with meta-analysis and meta-regression. DATA SOURCES:MEDLINE, EMBASE, CINHAL, CENTRAL and trial registries were searched up to 25 July 2018. STUDY SELECTION:We included randomised controlled trials (≥12 months' follow-up) evaluating the effects of multifactorial interventions on falls in older people aged 65 years and over, living in the community, compared with either usual care or usual care plus advice. REVIEW METHODS:Two authors independently verified studies for inclusion, assessed risk of bias and extracted data. Rate ratios (RaR) with 95% CIs were calculated for rate of falls, risk ratios (RR) for dichotomous outcomes and standardised mean difference for continuous outcomes. Data were pooled using a random effects model. The Grading of Recommendations, Assessment, Development and Evaluation was used to assess the quality of the evidence. RESULTS:We included 41 trials totalling 19 369 participants; mean age 72-85 years. Exercise was the most common prespecified component of the multifactorial interventions (85%; n=35/41). Most trials were judged at unclear or high risk of bias in ≥1 domain. Twenty trials provided data on rate of falls and showed multifactorial interventions may reduce the rate at which people fall compared with the comparator (RaR 0.79, 95% CI 0.70 to 0.88; 20 trials; 10 116 participants; I2=90%; low-quality evidence). Multifactorial interventions may also slightly lower the risk of people sustaining one or more falls (RR 0.95, 95% CI 0.90 to 1.00; 30 trials; 13 817 participants; I2=56%; moderate-quality evidence) and recurrent falls (RR 0.88, 95% CI 0.78 to 1.00; 15 trials; 7277 participants; I2=46%; moderate-quality evidence). However, there may be little or no difference in other fall-related outcomes, such as fall-related fractures, falls requiring hospital admission or medical attention and health-related quality of life. Very few trials (n=3) reported on adverse events related to the intervention. Prespecified subgroup analyses showed that the effect on rate of falls may be smaller when compared with usual care plus advice as opposed to usual care only. Overall, heterogeneity remained high and was not explained by the prespecified characteristics included in the meta-regression. CONCLUSION:Multifactorial interventions (most of which include exercise prescription) may reduce the rate of falls and slightly reduce risk of older people sustaining one or more falls and recurrent falls (defined as two or more falls within a specified time period). TRIAL REGISTRATION NUMBER:CRD42018102549.